The Art of Identification : Forensics, Surveillance, Identity - Purdon, James, 1983-; Littlefield, Melissa M., 1979-; Ferguson, Rex, 1977- (Book collections on Project MUSE., 2021)
"A multidisciplinary collection of essays exploring current scholarship on the history of human identification. Examines how techniques of identification are entangled within a wider sphere of cultural identity formation"--